Crosstalk Communications Between Islets Cells and Insulin Target Tissue: The Hidden Face of Iceberg - Langlois, Allan; Dumond, Aurore; Vion, Julie; Pinget, Michel; Bouzakri, Karim (Frontiers in Endocrinology, 2022)
The regulation of insulin secretion is under control of a complex inter-organ/cells crosstalk involving various metabolites and/or physical connections. In this review, we try to illustrate with current knowledge how β-cells communicate with other cell types and organs in physiological and pathological contexts. Moreover, this review will provide a better understanding of the microenvironment and of the context in which β-cells exist and how this can influence their survival and function. Recent studies showed that β-cell insulin secretion is regulated also by a direct and indirect inter-organ/inter-cellular communication involving various factors, illustrating the idea of “the hidden face of the iceberg”. Moreover, any disruption on the physiological communication between β-cells and other cells or organs can participate on diabetes onset. Therefore, for new anti-diabetic treatments’ development, it is necessary to consider the entire network of cells and organs involved in the regulation of β-cellular function and no longer just β-cell or pancreatic islet alone. In this context, we discuss here the intra-islet communication, the β-cell/skeletal muscle, β-cell/adipose tissue and β-cell/liver cross talk.